Shp2 signaling suppresses senescence in PyMT‐induced mammary gland cancer in mice. (3rd March 2015) - Lan, Linxiang; Holland, Jane D; Qi, Jingjing; Grosskopf, Stefanie; Vogel, Regina; Györffy, Balázs; Wulf‐Goldenberg, Annika; Birchmeier, Walter
Abstract In this study, we have used techniques from cell biology, biochemistry, and genetics to investigate the role of the tyrosine phosphatase Shp2 in tumor cells of MMTV‐PyMT mouse mammary glands. Genetic ablation or pharmacological inhibition of Shp2 induces senescence, as determined by the activation of senescence‐associated β‐gal (SA‐β‐gal), cyclin‐dependent kinase inhibitor 1B (p27), p53, and histone 3 trimethylated lysine 9 (H3K9me3). Senescence induction leads to the inhibition of self‐renewal of tumor cells and blockage of tumor formation and growth. A signaling cascade was identified that acts downstream of Shp2 to counter senescence: Src, focal adhesion kinase, and Map kinase inhibit senescence by activating the expression of S‐phase kinase‐associated protein 2 (Skp2), Aurora kinase A (Aurka), and the Notch ligand Delta‐like 1 (Dll1), which block p27 and p53. Remarkably, the expression of Shp2 and of selected target genes predicts human breast cancer outcome. We conclude that therapies, which rely on senescence induction by inhibiting Shp2 or controlling its target gene products, may be useful in blocking breast cancer.